Effectiveness and student teachers' perceptions of digital materials in enhancing vocabulary learning among rural primary students / Audrey A. Bernard Ining, Yoon Sook Jhee and Lee Kean Wah - Bernard, Audrey A.; Yoon, Sook Jhee; Wah, Lee Kean (UPENA, 2015)
This paper provides insights on the application of digital materials which are developed based on Luckin's Ecology of Resources to enhance the vocabulary learning among rural primary students in Sabah. The paper aims to share the preliminary findings on the effectiveness of the digital materials developed and to objectively investigate the student teachers' perceptions on digital materials. The web-based authoring tools used to develop the digital materials in the research were PowToon, Prezi and Video Scribe. These authoring tools include aspects such as animation, audios, photos, graphics and video creation. The project was conducted in Bundu Tuhan Primary School which is located in the interior area of Ranau. Among the participants involved are primary students from Year One to Year Three classes as well as a group of 14 student teachers from the TESL programme of University Malaysia Sabah. Research data were collected by using quantitative instruments which included both pre and post-tests as well as survey questionnaire.